2017
DOI: 10.1016/j.msec.2016.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired fully physically cross-linked double network hydrogels with a robust, tough and self-healing structure

Abstract: The conventional covalently cross-linked double network (DN) hydrogels with high stiffness often show low toughness and self-healing property due to the irreversible bond breakages in their networks. Therefore, scarcity of hydrogels that possess simultaneous features of stiffness, toughness, and autonomous self-healing properties at the same time remains a great challenge and seriously limits their biomedical applications. While, many natural materials acquire these features from their dynamic sacrificial bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 47 publications
(89 reference statements)
1
44
0
Order By: Relevance
“…(a) that the tensile strength of the PAA‐Fe 3+ (0.20)/Gelatin5%/PVA10% triple‐network hydrogel could reach 186.1 kPa, which is significantly higher than that of single‐ or double‐network hydrogels. This is attributed to a multi‐energy dissipative mechanism . It can be also observed from Fig.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…(a) that the tensile strength of the PAA‐Fe 3+ (0.20)/Gelatin5%/PVA10% triple‐network hydrogel could reach 186.1 kPa, which is significantly higher than that of single‐ or double‐network hydrogels. This is attributed to a multi‐energy dissipative mechanism . It can be also observed from Fig.…”
Section: Resultsmentioning
confidence: 83%
“…And the reversibility of metal coupling also gives the hydrogels good self‐healing properties. Sabzi et al . synthesized physically crosslinked agar/poly(vinyl alcohol) double‐network hydrogels, and found that the modulus and toughness can reach 200 kPa and 2200 kJ m −2 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…To measure the self‐healing property, hydrogel samples with different water contents (20, 40 and 60 wt%) were cut into two parts; the two cut surfaces were kept firmly in contact and stored in sealed sample bags to prevent loss of water from the samples, which were kept at room temperature for 24 h. The mechanical properties of the healed samples were measured and compared with the mechanical properties of the original sample to study the self‐healing property . The healing efficiency was thus calculated from the ratio of the tensile strength of the healed sample to that of the original sample (expressed as a percentage).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, DN hydrogels are composed of two networks: the first one, as the brittle gel, is generally high density and crosslinked, and the second one, the loose and stretchable network, is loosely crosslinked or is not even crosslinked. Furthermore, the molar concentration of the second network must be more than 20–30 times that of the first network . This structure can be synthesized with a general consecutive two‐step method.…”
Section: Introductionmentioning
confidence: 99%